2017
DOI: 10.1038/s41598-017-09079-3
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic immunomodulatory mechanisms triggered by Human Papillomavirus transformed cells: a potential role for G-CSF and neutrophils

Abstract: Cervical cancer is the last stage of a series of molecular and cellular alterations initiated with Human Papillomavirus (HPV) infection. The process involves immune responses and evasion mechanisms, which culminates with tolerance toward tumor antigens. Our objective was to understand local and systemic changes in the interactions between HPV associated cervical lesions and the immune system as lesions progress to cancer. Locally, we observed higher cervical leukocyte infiltrate, reflected by the increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 46 publications
4
45
1
5
Order By: Relevance
“…Investigating patients from a cohort enrolled at the Hospital das Clínicas in São Paulo (Table A), we observed that the plasmatic lactate concentration was significantly higher in patients with low‐ and high‐grade cervical lesions and cervical cancer than in individuals without cervical lesions (Fig. A).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Investigating patients from a cohort enrolled at the Hospital das Clínicas in São Paulo (Table A), we observed that the plasmatic lactate concentration was significantly higher in patients with low‐ and high‐grade cervical lesions and cervical cancer than in individuals without cervical lesions (Fig. A).…”
Section: Resultsmentioning
confidence: 95%
“…The use of the glycolytic pathway leads to the production of lactate that can be secreted and either displays a role as signaling molecule or used as a carbon source by other cells. 26,27 Investigating patients from a cohort enrolled at the Hospital das Clínicas in São Paulo (Table 1A), 28 we observed that the plasmatic One of the main signaling pathways that ensures cell viability and drives metabolism in cancer cells is the PI3K/Akt. 29,30 Although we were not able to measure the activity of this pathway in the previously described cohort, we analyzed this pathway, in a cohort of patients with high-grade cervical lesions and cervical cancer (enrolled through the Instituto do Câncer do Estado de São Paulo).…”
Section: Patients' Plasma Lactate Concentrations Increase According Tmentioning
confidence: 99%
“…The existence of such a variety of immunosuppressive mechanisms might be related to the many different types of immunosuppressive neutrophil populations, conditioned by external factors. Cytokines such as IFN‐ γ and granulocyte–macrophage colony‐stimulating factor, or the direct contact with mesenchymal stem cells or tumour cells, have all been proposed to induce a suppressive phenotype in neutrophils from healthy donors. In this context, evidence that immunosuppressive neutrophil populations are present in the spleen, placenta, airways, or in tumours, already exists, but our understanding of the relationship between circulating and tissue neutrophils is still in its infancy.…”
Section: Neutrophils and T Cellsmentioning
confidence: 99%
“…HPV employs multiple strategies for immune evasion, such as low virulence, interference with host cell‐cycle regulators, and inhibition of important components of the innate immune system . Consequently, HPV infection favors the establishment of an immune tolerogenic environment and the progression of cervical lesions and cancer …”
Section: Introductionmentioning
confidence: 99%